2022
DOI: 10.1021/acssynbio.2c00151
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytically Activated CRAC Effectors through Designed Intramolecular Inhibition

Abstract: Highly regulated intracellular calcium entry affects numerous cellular physiological events. External regulation of intracellular calcium signaling presents a great opportunity for the artificial regulation of cellular activity. Calcium entry can be mediated by STIM proteins interacting with Orai calcium channels; therefore, the STIM1–Orai1 pair has become a tool for artificially modulating calcium entry. We report on an innovative genetically engineered protease-activated Orai activator called PACE. CAD self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A defined protease that can be chemically regulated was able to cleave the inhibitory coiled-coil pairs, triggering oligomerization and activation of PACE2 ( Figure 2 C), as evidenced by Ca 2+ imaging studies. Jazbec et al [ 242 ] developed a library of PACE constructs. They demonstrated that direct attachment of CAD to the TEV cleavage site and then to the coiled-coil domain leads to spontaneous activation, but it is maintained in the inactive state by the additional insertion of a peptide with a high helical propensity.…”
Section: Synthetic Biology Application To Crac Channels and Impact On...mentioning
confidence: 99%
See 2 more Smart Citations
“…A defined protease that can be chemically regulated was able to cleave the inhibitory coiled-coil pairs, triggering oligomerization and activation of PACE2 ( Figure 2 C), as evidenced by Ca 2+ imaging studies. Jazbec et al [ 242 ] developed a library of PACE constructs. They demonstrated that direct attachment of CAD to the TEV cleavage site and then to the coiled-coil domain leads to spontaneous activation, but it is maintained in the inactive state by the additional insertion of a peptide with a high helical propensity.…”
Section: Synthetic Biology Application To Crac Channels and Impact On...mentioning
confidence: 99%
“…This tool was valuable to trigger Ca 2+ entry, NFAT activation, and associated downstream signaling events. The latter was demonstrated by protease cleavage-triggered expression of the cytokine IL-2, which is an essential cytokine governing T cell growth, the differentiation of regulatory T cells, and induction of cell death, as well as TNFα, which is an essential cytokine involved in the immune response, in Jurkat T cells [ 242 ]. Despite these valuable effects, further studies are needed to determine how fast PACE can be activated and whether its Ca 2+ currents correspond to those of CRAC channels.…”
Section: Synthetic Biology Application To Crac Channels and Impact On...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using coiled coils for domain inhibition and proteolytic regulation, Jazbec et al [42] reported an innovative genetically engineered protease-activated Orai calcium channels activator called PACE-a genetically engineered mediator between proteolytic activity and calcium influx (Figure 3d). In this study, a part of STIM protein (which together with Orai1 channels modulates calcium entry) termed CAD was engineered.…”
Section: Coiled Coil-mediated Signaling Circuitsmentioning
confidence: 99%